Non-Traditional Approaches to Weather Observations in Developing Countries - Snow, John T. (International Finance Corporation, Washington, DC, 2017)
In many developing countries, given their poor economic circumstances, weather observing networks are usually installed using funds from international development and aid agencies to enhance the capability of local national hydro-meteorological services (NHMS) and to accomplish humanitarian objectives. This paper discusses non-traditional approaches for establishing sustainable weather observing networks in developing countries, beginning with a brief overview of the importance of data from such networks to a NHMS. Some of the challenges inherent in establishing and maintaining weather and climate observing networks in developing countries are described. This is followed by a discussion of how these challenges may be addressed through the development of weather observing networks based on facilities and capabilities of the local cellular telephone network, such as the open lattice tower pictured in the background of the cover photograph. The paper reviews and summarizes currently available scientific, technical, and commercial literature regarding use of cell phone towers as observing sites. It provides a few illustrative examples of non-traditional technologies well-suited to making cell-tower based observations. The paper concludes with recommendations concerning how one may work with NHMSs in developing countries to improve the sustainability of their observing networks. These recommendations are focused on partnerships, in the sense of true business relationships, involving the NHMSs with, for example, local telephone companies, other in-country utilities, and commercial and private sector instrument manufacturers and data services. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.